EFFECT OF DIFFERENT SOLVENT AND TIME EXTRACTION TO CAROTENOID ANTIOXIDANT ACTIVITY FROM CRAB SHEL(Scylla olivacea) - Harry Sihombing; Suparmi '; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study aimed to evaluate the effect of different solvent (Aceton,Heksane and Ethanol) and long extraction times (2, 3, 4 hours) to the antioxidantactivity of carotenoids from crab shell (Scylla olivacea). A total of 7 kg of crabshells was minced. Carotenoid extracts was obtained from crab shell flour (100 g)and dissolved in 500 ml of solvent (Aceton, Heksane and Ethanol)Carotenoid extract was observed for total carotenoids, rendement extract,the intensity of color (L, a, b), pH and antioxidant activity assay. Optimalconditions for the extraction process was obtained in aceton solvent (A1) with 4hof long extraction time (B3), with a total carotenoid 16,27 ug / g, yield 20,64 gextract, the intensity of color (L, a, b) 38,07; +12,60; and +12,80 respectively, pH7,3 and antioxidant activity (DPPH) 89,75 ppm.Keywords: The type of solvent, long extraction times, the carotenoidantioxidan activity, crab shell.